2013
DOI: 10.1007/s00101-013-2276-5
|View full text |Cite
|
Sign up to set email alerts
|

Berufsbild des Anästhesisten in der Öffentlichkeit

Abstract: Unfortunately, the perception of patients on the versatility and characteristics of anesthetists are poorly developed. However, the knowledge differs significantly depending on previous experience and gathered information. Interestingly patients with previous experience mostly showed better knowledge compared to interested patients. Results suggest that personal interaction, patient-physician communication in general and improved collaboration between general practitioners and anesthetists are the key elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Subsequently, the patient’s levels of knowledge about anaesthesia practices and the anaesthetist were evaluated, and it was found that past experiences did not affect the patient’s knowledge levels. Baja et al 20 identified that the level of knowledge about anaesthesia increased along with past experiences, and the patients who had anaesthesia before had higher levels of knowledge than those who were curious about anaesthesia. However, in the current study, it was found that experience did not affect the level of knowledge about anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the patient’s levels of knowledge about anaesthesia practices and the anaesthetist were evaluated, and it was found that past experiences did not affect the patient’s knowledge levels. Baja et al 20 identified that the level of knowledge about anaesthesia increased along with past experiences, and the patients who had anaesthesia before had higher levels of knowledge than those who were curious about anaesthesia. However, in the current study, it was found that experience did not affect the level of knowledge about anaesthesia.…”
Section: Discussionmentioning
confidence: 99%